Large pore size and controlled mesh elongation are relevant predictors for mesh integration quality and low shrinkage – Systematic analysis of key parameters of meshes in a novel minipig hernia model. (October 2015) - Weyhe, Dirk; Cobb, William; Lecuivre, Julie; Alves, Antoine; Ladet, Sebastien; Lomanto, Davide; Bayon, Yves
Abstract: Background: Prosthetic mesh implants in hernia repair are frequently used based on the fact that lower recurrence rates are detected. However, an undesirable side effect is persistent foreign body reaction that drives adhesions and shrinkage among other things in the course of time. Thereby a variety of meshes have been created in an attempt to alleviate these side effects, and particular relating to shrinkage, the ideal mesh has not been developed. Large pore size is one of the properties to get better ingrowth of the implants but could also be a risk factor to shrinkage behavior. The aim of this preclinical study was to determine optimal pore size based on mesh integration and shrinkage in a hernia minipig model. Methods: Twenty female minipigs were each implanted at four abdominal retromuscular sites with meshes (designed and knitted specifically for this study) that had various weights and pore sizes, but similar weave. At 3 and 21 weeks post-operation, ten pigs each were euthanized. Mesh integration and shrinkage were evaluated through macroscopic observation, biomechanical testing and histopathological analysis. Results: The large pore meshes (6.1–6.6 mm 2 ) showed significantly better integration than small pore (0.9–1.1 mm 2 ) counterparts, by biomechanical testing and histological assessment. This was independent of mesh weight. The lightweight small pore mesh exhibited significantly more shrinkage than any of the other meshes, while the three-dimensional heavyweight large pore mesh exhibited the least shrinkage. Mesh shrinkage and elongation at 50 Newton (N) as one parameter of the implant structural stability appeared to be strongly interrelated. Conclusion: Tissue ingrowth of meshes depends on increasing pore size. Macroporous mesh design >1.5 mm diameter appears to be optimal in terms of mesh integration. Lightweight meshes with a large pore size on one hand and a lack of structural stability on the other hand drives mesh shrinkage. High stretchability (Elongation >50 N) induces higher shrinkage and therefore elongation at 50 N appears to be a new parameter to estimate mesh shrinkage. Three-dimensional mesh constructions relate to the lowest shrinkage behavior caused by higher structure stability. Highlights: Larger pore size (>1.5 mm) leads to better integration and biomechanical capacity. Large pore size and lack of stability in lightweight meshes lead to shrinkage. Mesh elongation at 50 N seems to be a new parameter to estimate shrinkage. 3D mesh construction leads to high structure stability and low shrinkage.